Changes in Burst and Spike Propgagtion Associated with Gap Junction Formation in Myometrium at Parturition - Miller, Michael Steven (My University, 1986)
The factors regulating the uterus in the maintenance of pregnancy and the onset of labor are two important and unresolved problems in uterine physiology. At term, specialized cell-to-cell contacts, gap junctions, appear between the uterine smooth muscle cells. These structures are thought to allow direct passage of ions and small molecules between cells thus their formation between uterine smooth muscle cells at term may promote propagation of electrical activity and development of contractile synchrony in the uterine wall, necessary for expulsions of the fetus(es). The objective of this thesis was to examine the possible functional role of gap junction formation in the myometrium at parturition. The hypothesis that gap junction formation results improved electrical excitation (which give an indirect measure of cell-to-cell electrical coupling_ in the myometrium before (i.e. at preterm) and after (i.e. at delivery) in situ gap junction formation. Some of the tissues used for these experiments were examined by thin section electron microscopy for the presence of gap junctions. Spontaneous burst discharges propagated other the entire recording distance of 15mm in the longitudinal axis of the myometrium at both preterm and at parturition. Burst activity at both times showed some of the characteristics of a system of coupled relaxation oscillators. However, individual spikes within the bursts propagated further with higher velocity in this axis at parturition as compared to at preterm. In the transverse axis of the myometrium, both bursts and individual spikes within bursts propagated over longer distances at parturition than before. Propagation in this axis at parturition appeared to require an intact or undamaged circular muscle layer. Analysis of the propagation of spikes evoked by electrical stimulation confirmed that spike propagation was improved (e.g. higher velocity and long distance spread) in both the longitudinal and transverse axes of the myometrium at parturition. Electron microscopy studies confirmed that gap junctions were present in large numbers between uterine smooth muscle cells during parturition and were absent or present in very small numbers at preterm. Thus, improved propagation of electrical discharges was associated with an increase in gap junction contact between myometrial cells. These results are consistent with the hypothesis that gap junction formation at the term results in improved electrical coupling of the uterine smooth muscle cells.
Keywords: Medicine and Health Sciences; Medicine and Health Sciences